2006
DOI: 10.1099/ijs.0.63914-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides intestinalis sp. nov., isolated from human faeces

Abstract: During studies of the microbiota of human faeces, five strains of Gram-negative anaerobic rods were isolated following growth in a polyamine-deficient medium. These strains belonged to the genus Bacteroides on the basis of 16S rRNA gene sequence data. 16S rRNA gene sequence similarity between one of the strains, 341 T , and recognized species within the genus Bacteroides was <95 %. The DNA G+C content (44 mol%) and major fatty acid composition (anteiso-C 15 : 0 , 32?0 %) supported the affiliation of strain 341… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…Moreover, although cholesterol-reducing activity has never been reported in the genus Bacteroides, steroid metabolism, including bile salt hydrolase, sulfatase, and glucuronidase activities, has been detected in different Bacteroides species (25). Sequences from novel phylotypes of yet-to-be-cultured Bacteroides species have been detected in 16S rRNA gene clone libraries from human fecal samples (11,37), and previously unknown Bacteroides species of human origin have recently been isolated and characterized (1,2,19). A comparison of 16S rRNA gene sequences revealed that the cholesterol-reducing strain D8 clustered with the two isolates described as B. dorei, displaying ÏŸ99.5% sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although cholesterol-reducing activity has never been reported in the genus Bacteroides, steroid metabolism, including bile salt hydrolase, sulfatase, and glucuronidase activities, has been detected in different Bacteroides species (25). Sequences from novel phylotypes of yet-to-be-cultured Bacteroides species have been detected in 16S rRNA gene clone libraries from human fecal samples (11,37), and previously unknown Bacteroides species of human origin have recently been isolated and characterized (1,2,19). A comparison of 16S rRNA gene sequences revealed that the cholesterol-reducing strain D8 clustered with the two isolates described as B. dorei, displaying ÏŸ99.5% sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genera Bacteroides and Parabacteroides in the order Bacteroidales are known to make up 14 to 40% of cultivable microorganisms in human feces (21 (3,12,23,26,38) and constitute up to 80% of the fecal bacterial isolates from the genus Bacteroides documented in Ribosomal Database Project II (http://rdp.cme.msu.edu).…”
Section: Approximately 10mentioning
confidence: 99%
“…For both strains, the most closely related type strain was Bacteroides coprosuis CCUG 50528 T (Whitehead et al, 2005), with a sequence similarity of 95.9 % based on the sequence of strain SV434 T (the aforementioned Y was replaced with T for the similarity calculations). The next most closely related type strains were those of Bacteroides intestinalis (Bakir et al, 2006) (sequence similarity, 93.5 %) and Bacteroides thetaiotaomicron (93.2 %) (Holdeman et al, 1984). Strains SV434 T and S562 formed a branch that was separate from those of closely related Bacteroides species in the phylogenetic tree composed of related Bacteroides species (Fig.…”
mentioning
confidence: 99%
“…(Bakir et al, 2006); 4, B. thetaiotaomicron ATCC 29148 T (Holdeman et al, 1984). +, Positive; 2, negative; ND, no data available.…”
mentioning
confidence: 99%